Los Títeres en la Lectura Comprensiva del Tercer Grado de la Unidad Educativa Padre Julián Lorente, de la ciudad de Loja, 2022- 2023 - Caicedo Saez, Rosa Angélica (2023)
The present research is about: Puppets in Reading Comprehension for Third Grade students at the Padre Julián Lorente School in the city of Loja, 2022-2023. The general objective is to determine the impact of puppets on teaching reading comprehension for Third Grade students at the Padre Julián Lorente School in the city of Loja, 2022-2023. To achieve this, three specific objectives were proposed: the first one was to diagnose the level of reading comprehension of Third Grade students; the second one was to develop a proposal using puppets to strengthen reading comprehension in Third Grade students; and the third one was to evaluate the impact of using puppets on the improvement of reading comprehension in Third Grade students. The methodology used was a mixed approach, descriptive research type, non- experimental design, analytical, synthetic, and hermeneutic method, with techniques such as observation and survey, and instruments such as interviews and pre- and post-evaluative questionnaires. The population consisted of 16 students and 1 teacher. The study concludes that the use of puppets in reading comprehension is beneficial, as it captures the students' attention and helps them overcome shyness, allowing them to become actively involved in the story or reading and leading to a significant improvement in their level of reading comprehension in the Third Grade. Keywords: Puppets, Reading Comprehension, Levels of Reading Comprehension, Teacher, Student.